Competitive Redox Chemistries in Vanadium Niobium Oxide for Ultrafast and Durable Lithium Storage - Ding, Xiaobo; Lin, Jianhao; Huang, Huiying; Zhao, Bote; Xiong, Xunhui (Nano-Micro Letters, 2023)
Niobium pentoxide (Nb2O5) anodes have gained increasing attentions for high-power lithium-ion batteries owing to the outstanding rate capability and high safety. However, Nb2O5 anode suffers poor cycle stability even after modified and the unrevealed mechanisms have restricted the practical applications. Herein, the over-reduction of Nb5+ has been demonstrated to be the critical reason for the capacity loss for the first time. Besides, an effective competitive redox strategy has been developed to solve the rapid capacity decay of Nb2O5, which can be achieved by the incorporation of vanadium to form a new rutile VNbO4 anode. The highly reversible V3+/V2+ redox couple in VNbO4 can effectively inhibit the over-reduction of Nb5+. Besides, the electron migration from V3+ to Nb5+ can greatly increase the intrinsic electronic conductivity for VNbO4. As a result, VNbO4 anode delivers a high capacity of 206.1 mAh g−1 at 0.1 A g−1, as well as remarkable cycle performance with a retention of 93.4% after 2000 cycles at 1.0 A g−1. In addition, the assembled lithium-ion capacitor demonstrates a high energy density of 44 Wh kg−1 at 5.8 kW kg−1. In summary, our work provides a new insight into the design of ultra-fast and durable anodes. Highlights: 1 The over-reduction from Nb5+ to Nb3+ in the lithiation process have been demonstrated to be the critical reason for the capacity decay of Nb2O5 for the first time. 2 A novel competitive redox strategy has been proposed to suppress the over-reduction of Nb5+ to Nb3+, which can be achieved by the incorporation of vanadium to form a new rutile VNbO4 anode. 3 The performance of VNbO4 anode designed in this study stands among the best in cycle stability.